Effectiveness of a technical support program with women’s self-help groups in catalyzing health and nutrition behaviors in Bihar—a multicomponent analysis - Sudipta Mondal; Indu Bisht; Santosh Akhauri; Indrajit Chaudhuri; Narottam Pradhan; Sweta Kumari; Shuchi Sree Akhouri; Rakesh Kumar Jha; Manoj Kumar Singh; Suman Das; Apollo Purty; Arko Mukherjee; et al. (Frontiers in Public Health)
IntroductionBihar Rural Livelihoods Promotion Society launched the JEEViKA program in 2007 to improve livelihoods through the Self-Help Group (SHG) platform. Women’s SHGs have shown members’ health improvements by promoting awareness, practices and access to services. This study investigates whether Health & Nutrition (HN) interventions delivered by JEEViKA Technical Support Program (JTSP) via SHG platforms could improve maternal and newborn health and nutritional behaviors in rural Bihar.MethodsAnnual Household Survey and Married Women of Reproductive Age (MWRA) studies of Bihar Technical Support Unit were used to analyze the effectiveness of JTSP on HN behaviors for mother and their infants in Bihar during 2016–21. Descriptive analysis followed by multivariable (binary and multinomial) logistic regressions were conducted to determine the distribution of and associations between various individual/community and programmatic exposures and outcomes of interest.ResultsDuring 2016–2021, in Bihar, statewide increase (32 to 47%) in SHG membership across all population strata and expansion of HN layering of JTSP from 101 to 349 blocks corroborated with improvements in Maternal-Newborn-Child Health & Nutrition (MNCHN) indicators in JTSP blocks and SHG members. Substantial increase was observed in ≥3ANC visit (9% points), institutional delivery (10%), skin-to-skin-care (17%), dry cord-care (23%), early initiation of breastfeeding (19%) & complementary feeding (9%). Adjusting for socio-demographic factors and Front-Line Workers’ (FLWs’) advice/counseling, multivariable logistic regression revealed that SHG member in JTSP blocks delivering post-intervention (2021) were more likely (vs 2016) to practice: ≥3ANC visits (Adjusted Odds Ratio: aOR = 1.48, p < 0.0001), institutional delivery (aOR = 1.71, p < 0.0001), skin-to-skin care (aOR = 3.16, p < 0.0001) and dry cord-care (aOR = 2.64, p < 0.0001), early initiation of breastfeeding (aOR = 1.61, p < 0.0001), complementary feeding (aOR6-8 months = 1.48, p < 0.0001) and minimum dietary diversity (aOR6-8 months = 1.24). Better mobility, decision making, economic independence and overall empowerment were also evident among SHG member MWRA as opposed to non-members after both phases.DiscussionThe results highlight successful HN integration in JEEViKA by JTSP, demonstrating its effectiveness in integrating with State Rural Livelihoods Mission community platforms. JTSP showcases collaboration within a government system and emphasizes systematic introduction and strengthening at multiple levels. This integration has enabled JEEViKA systems to self-sustain its own HN implementation processes, paving the way for cross-sectoral comprehensive delivery mechanisms for social development.